2014
DOI: 10.1371/journal.pone.0091633
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Season and Management Affect Fecal Glucocorticoid Metabolite Concentrations in Captive Goral (Naemorhedus griseus) in Thailand

Abstract: Chinese goral (Naemorhedus griseus) are a threatened species in Thailand and the focus of captive breeding for possible reintroduction. However, little is known of their biology or what factors in the captive environment affect welfare. Our objective was to determine the impact of gender, season, and management on goral adrenal activity. We hypothesized that differences in fecal glucocorticoid concentrations would be related to animal density. Fecal samples were collected 3 days/week for 1 year from 63 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Other studies have shown varied results regarding sex-specific differences in FGM levels. A study in captive goral ( Naemorhedus griseus ), one of the muskox’s closest taxonomic relatives, described higher FGM levels in males ( Khonmee et al , 2014 ), but many other studies in ungulates report no difference between sexes (captive red deer ( Huber et al , 2003 ), free-ranging elk ( Millspaugh et al , 2001 ), free-ranging American bison ( Bison bison ) ( Ranglack et al , 2016 ), and captive black ( Diceros bicornis ) and white ( Ceratotherium simum ) rhinoceros ( Brown et al , 2001 )). Differences in FGM or hair GC levels between sexes may reflect distinct physiological and/or behavioural characteristics that certainly vary among species and across seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown varied results regarding sex-specific differences in FGM levels. A study in captive goral ( Naemorhedus griseus ), one of the muskox’s closest taxonomic relatives, described higher FGM levels in males ( Khonmee et al , 2014 ), but many other studies in ungulates report no difference between sexes (captive red deer ( Huber et al , 2003 ), free-ranging elk ( Millspaugh et al , 2001 ), free-ranging American bison ( Bison bison ) ( Ranglack et al , 2016 ), and captive black ( Diceros bicornis ) and white ( Ceratotherium simum ) rhinoceros ( Brown et al , 2001 )). Differences in FGM or hair GC levels between sexes may reflect distinct physiological and/or behavioural characteristics that certainly vary among species and across seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Active management of wildlife conservation strategies is necessary to ensure that ecosystems remain sustainable and intact. Tropical landscapes such as Thailand are globally important hotspots of biodiversity (e.g., Khonmee et al [2]), although endemic species are being confronted by dramatic habitat loss as a result of climate change and anthropogenic activity [3]. The Chinese goral (Naemorhedus griseus) is a goat-like wild ungulate that is predominantly distributed across China, India, Myanmar, Thailand, and Vietnam [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of potential stressors in zoo environments, including inadequate housing, inappropriate social management and poor husbandry ( Horton et al , 1991 ; Mellen, 1991 ; Perkins, 1992 ; Carlstead and Shepherdson, 1994 ; Saito et al , 1996 ; Wielebnowski et al , 2002 ; Huber et al , 2003 ; Shepherdson et al , 2004 ; Morgan and Tromborg, 2007 ; Moreira et al , 2007 ; Scarlata et al , 2013 ; Khonmee et al , 2014a ), many of which are associated with increased glucocorticoid production ( Liptrap, 1993 ; Möstl and Palme, 2002 ; Millspaugh and Washburn, 2004 ; Touma and Palme, 2005 ; Brown, 2006 ; Khonmee et al , 2014b ). One method commonly used to monitor adrenal activity as it pertains to welfare in wildlife species is the analysis of glucocorticoid metabolites excreted in urine and faeces ( Palme et al , 1996 ; Schwarzenberger et al , 1996 ; Brown, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In felids, because urine collection is difficult and glucocorticoids are primarily excreted in faeces ( Brown, 2006 ), most non-invasive assessments of adrenal function are based on faecal analyses ( Huber et al , 2003 ; Millspaugh and Washburn, 2004 ; Brown, 2006 ). However, adrenocortical responses to various stressors may be confounded by daily and seasonal variations in basal hormone production ( Millspaugh and Washburn, 2004 ; Allwin et al , 2014 ; Khonmee et al , 2014a , b ; Parnell et al , 2014 ). In addition, age can influence glucocorticoid secretion ( Vallée et al , 1999 ; Downs et al , 2008 ).…”
Section: Introductionmentioning
confidence: 99%